Community Participation in Green City Action Plan (Study about Implementation of Green City Development Program in Tulungagung) - Fadhila Putri Sakina; Sumartono Sumartono; Mohammad Nuh (Sekolah Pascasarjana Universitas Brawijaya, 2018)
A green city becomes the one of the adaptation strategies which is responsive to the impact of climate change. A green city is an urban development concept which puts forward aspects of sustainability. The placement of sustainable development as a basic principle of a green city, then demands the existence of the participation from the community. The objectives of this research were to describe and analyze community participation in Green City Action Plan in Tulungagung. This research used descriptive research method with qualitative approach and qualitative data analysis of interactive model. The research results showed that the community participation process could be formed because of the existence of community’s opportunity, ability and will to participate. Degree of community participation was on degree of participation. The existence of community’s willingness and the Central Government’s commitment to support the participation became the supporting factors. Meanwhile, the community’s dependence on the government and management which was not optimal yet became the inhibiting factors of participation.